Booking system of ICT equipment using barcode scanner - Mathanraja, Many (2014)
Booking System of ICT Equipment (BSIE) is a web-based system. This system is designed especially for the University Malaysia Pahang community which staff and student of UMP. Before this system being developed, the Booking System of ICT Equipment was integrated with E-Community system and without using barcode scanner. This causes the PTMK staff going through difficulty when the E-Community performances become low. Thus, this system develop to make their operation goes smoothly and can track the quantity equipment available than manually written. Apart from this, this system has reporting function which gives PTMK Staff to filling the daily progress of these activities. Besides this, the PTMK Staff also can download the report either to Excel file or PDF file. This all functions of the system allow the work of PTMK Staff easier.